(untitled) (Journal of Plant Disease Sciences, 2021)
Crosses were made between powdery mildew resistant and susceptible mungbean genotypes. The parents and progenies were screened for their reaction to powdery mildew disease and levels of biochemical parameters were determined at pre and post infection stage of the disease. Under field condition, the genotype (parent) Vaibhav and BPMR-48 exhibited resistant reaction to powdery mildew, while the genotype Kopargaon exhibited susceptible and SML-668 moderately susceptible reaction to the disease. Area under disease progress curve (AUDPC) assessment projected that the speed of disease development was slower in resistant than that of susceptible parents. Pathogenesis related biochemical studies clearly indicated that there was strong association of biochemical characters and disease score of the genotypes. The levels of enzymes (chitinase and polyphenol oxidase) and potash in resistant genotypes were high as compared to susceptible genotypes across the crosses at pre and post infection stages.